1965
DOI: 10.1111/j.1151-2916.1965.tb11806.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion Studies of the System FexO‐MgO

Abstract: The solid-state reaction between Fe,O and MgO is best described as counterdiffusion of the magnesium and iron ions through a relatively rigid oxygen ion lattice of the rock salt structure. A relation between a mutual diffusion coefficient and a controlled cation vacancy concentration was determined by an analysis of the concentration-penetration curve of the Fe,O-MgO solid solution. The diffusion coefficient increased approximately exponentially with a linear increase of the cation vacancy concentration. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…29,[33][34][35] The diffusion rate of atomics is proportional to the jump frequency. 34,35 In other words, each position of Fe 3+ substitutent could be a available site for the Zr 4+ ion migration if the interstitial migration of Fe 3+ ions could operate during the sintering process. Therefore, the interstitial defects of Fe 3+ ions partially contribute to an increase in the diffusion coefficient D.…”
Section: Discussionmentioning
confidence: 99%
“…29,[33][34][35] The diffusion rate of atomics is proportional to the jump frequency. 34,35 In other words, each position of Fe 3+ substitutent could be a available site for the Zr 4+ ion migration if the interstitial migration of Fe 3+ ions could operate during the sintering process. Therefore, the interstitial defects of Fe 3+ ions partially contribute to an increase in the diffusion coefficient D.…”
Section: Discussionmentioning
confidence: 99%
“…A study of interdiffusion of the Fe x O-MgO system at 1578 K by Rigby and Cutler [15] showed that the mutual diffusion coefficient of Mg 2ϩ and iron ions (Fe 3ϩ and Fe 2ϩ ) increased exponentially with the cation vacancy concentration. Under more oxidized conditions, the counterdiffusion of Mg 2ϩ and iron ions (Fe 3ϩ and Fe 2ϩ ) would be faster.…”
Section: A Interfacial Reactions Between Mgo and Calcium Ferrite Slagsmentioning
confidence: 99%
“…So, a tailing of concentration, which usually appears in diffusion phenomena, was not observed. Though these concentration profiles are of an unusual form, the same profile was observed in the system FexO-MgO by Rigby et al (9).…”
Section: Reaction In the System Al2o3-mn3o4mentioning
confidence: 68%